2009
DOI: 10.1373/clinchem.2008.119669
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C for Enhancement of Risk Stratification in Non–ST Elevation Acute Coronary Syndrome Patients with an Increased Troponin T

Abstract: BACKGROUND:We assessed the value of cystatin C for improvement of risk stratification in patients with non-ST elevation acute coronary syndrome (nSTE-ACS) and increased cardiac troponin T (cTnT), and we compared the long-term effects of an early invasive treatment strategy (EIS) with a selective invasive treatment strategy (SIS) with regard to renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
0
34
1
Order By: Relevance
“…Recently, these observations have been confirmed and expanded by investigators in the ICTUS (Invasive vs Conservative Treatment in Unstable Coronary Syndromes) trial, in which Windhausen et al found that in patients with NSTE-ACS and increased cardiac troponin T concentrations, high plasma cystatin C concentrations are associated with a higher risk of death and spontaneous MI (38 ).…”
Section: Findings In Acute Coronary Syndrome Patientsmentioning
confidence: 82%
“…Recently, these observations have been confirmed and expanded by investigators in the ICTUS (Invasive vs Conservative Treatment in Unstable Coronary Syndromes) trial, in which Windhausen et al found that in patients with NSTE-ACS and increased cardiac troponin T concentrations, high plasma cystatin C concentrations are associated with a higher risk of death and spontaneous MI (38 ).…”
Section: Findings In Acute Coronary Syndrome Patientsmentioning
confidence: 82%
“…[25][26][27] Moreover, increased cystatin C was associated with all-cause, cardiovascular, and even non-cardiovascular mortality in a population-based cohort of subjects with normal kidney function. 28 However, whether cystatin C merely reflects the association of mildly impaired kidney function with increased risk of cardiovascular disease, or is an independent risk factor involved in the pathogenesis of atherosclerosis, has not been fully elucidated.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 97%
“…Even a small decrease in GFR estimated by C-G, MDRD, or cystatin C is associated with an increased risk for death and cardiovascular disease (7,8,(11)(12)(13)(14)(15)(16)(17). Concentrations of cystatin C have been related to both mortality and myocardial infarction rates in a non-STelevation acute coronary syndrome (NSTE-ACS) population (16 ).…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%